Advancements in the Diagnosis and Treatment of Hypertrophic Cardiomyopathy: A Comprehensive Review - Randeep Gill; Arsalan Siddiqui; Brianna Yee; Michael V. DiCaro; Nazanin Houshmand; Tahir Tak (Journal of Cardiovascular Development and Disease)
Hypertrophic cardiomyopathy (HCM) is characterized by excessive growth of myocardial tissue, most commonly due to genetic mutations in sarcomere proteins. This can lead to complications such as heart failure, mitral regurgitation, syncope, arrhythmias, sudden cardiac death, and myocardial ischemia. While we have come a long way in our understanding of the pathophysiology, genetics, and epidemiology of HCM, the past 10 years have seen significant advancements in diagnosis and treatment. As the body of evidence on hypertrophic cardiomyopathy continues to grow, a comprehensive review of the current literature is an invaluable resource in organizing this knowledge. By doing so, the vast progress that has been made thus far will be widely available to all experts in the field. This review provides a comprehensive analysis of the scientific literature, exploring both well-established and cutting-edge diagnostic and therapeutic options. It also presents a unique perspective by incorporating topics such as exercise testing, genetic testing, radiofrequency ablation, risk stratification, and symptomatic management in non-obstructive HCM. Lastly, this review highlights areas where current and future research is at the forefront of innovation in hypertrophic cardiomyopathy.